Evaluating the process of practice enhancement for exclusive breastfeeding (PEEB): a participatory action research approach for clinical innovation - Elaine Lehane; Catherine Buckley; Helen Mulcahy; Elizabeth McCarthy; Liz Cogan; Rhona O'Connell; Margaret Murphy; Patricia Leahy-Warren (BMC, 2024)
Abstract Background Despite the known benefits of exclusive breastfeeding, global rates remain below recommended targets, with Ireland having one of the lowest rates in the world. This study explores the efficacy of Participatory Action Research (PAR) and Work-Based Learning Groups (WBLGs) to enhance breastfeeding practices within Irish healthcare settings from the perspective of WBLG participants and facilitators. Methods Employing a PAR approach, interdisciplinary healthcare professionals across maternity, primary, and community care settings (n = 94) participated in monthly WBLGs facilitated by three research and practice experts. These sessions, conducted over nine months (November 2021 - July 2022), focused on critical reflective and experiential learning to identify and understand existing breastfeeding culture and practices. Data were collected through participant feedback, facilitator notes, and reflective exercises, with analysis centered on participant engagement and the effectiveness of WBLGs. This approach facilitated a comprehensive understanding of breastfeeding support challenges and opportunities, leading to the development of actionable themes and strategies for practice improvement. Results Data analysis from WBLG participants led to the identification of five key themes: Empowerment, Ethos, Journey, Vision, and Personal Experience. These themes shaped the participants' meta-narrative, emphasising a journey of knowledge-building and empowerment for breastfeeding women and supporting staff, underlining the importance of teamwork and multidisciplinary approaches. The project team's evaluation highlighted four additional themes: Building Momentum, Balancing, Space Matters, and Being Present. These themes reflect the dynamics of the PAR process, highlighting the significance of creating a conducive environment for discussion, ensuring diverse engagement, and maintaining energy and focus to foster meaningful practice changes in breastfeeding support. Conclusion This study highlights the potential of WBLGs and PAR to enhance the understanding and approach of healthcare professionals towards breastfeeding support. By fostering reflective and collaborative learning environments, the study has contributed to a deeper understanding of the challenges in breastfeeding support and identified key areas for improvement. The methodologies and themes identified hold promise to inform future practice and policy development in maternal and child health.